TEACHING GRAMMAR IN CONTEXT: EFFECTS ON ACCURACY AND LEARNER ENGAGEMENT - Ziyoda Saparbayeva Rustamboy qizi (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Traditional grammar instruction often relies on isolated drills and rote memorization, which may fail to translate into communicative competence. In contrast, teaching grammar in context involves presenting grammatical forms through meaningful use in real-life or simulated communicative situations. This article explores the theoretical foundations, pedagogical benefits, and practical strategies for contextual grammar instruction. It also examines its effects on grammatical accuracy and learner engagement. Research suggests that grammar taught through contextualized input and output leads to better retention, higher learner motivation, and improved application of grammar in authentic communication. Challenges such as curriculum constraints and teacher preparedness are discussed, along with strategies to address them.